Risk factors for in-hospital mortality from visceral leishmaniasis: A case-control study - Ingrid V. Oliveira-Sena; Guilherme L. Werneck (Elsevier, 2020)
Background: The timely identification of visceral leishmaniasis (VL) patients with a higher risk of death is essential for meeting the target of reducing case-fatality rates in the Americas. This study aimed to identify factors associated with death from VL in the State of Piaui, Brazil. Methods: Case-control study evaluating the following putative risk factors for death from VL: gender and age of the patient, local of residence, signs, and symptoms, laboratory data, comorbidities and days of evolution of the disease. The associations between risk factors and death were expressed as odds ratios and their respective 95% confidence intervals. Results: In the period analyzed a total of 2525 VL patients were admitted to the hospital, corresponding to 9,3% of all VL admissions in Brazil. Among them, 177 patients died (case-fatality rate of 7.0%). In the multivariate analysis the following variables showed a statistically significant association with death: ≥60 years, vomiting, edema, diarrhea, platelets < 50.000/mm³, jaundice, splenomegaly, and pneumonia. Conclusions: The identified factors associated to death from VL can be easily assessed at the time of or up to 48 h after admission and may be used to inform clinical decisions, improving the clinical and laboratory monitoring of patients. Keywords: Visceral leishmaniasis, Case-control, Deaths